Interim result of phase II, prospective, single-arm trial of long-course chemoradiotherapy combined with concurrent tislelizumab in locally advanced rectal cancer - Gao, Jiale; Zhang, Xiao; Yang, Zhengyang; Zhang, Jie; Bai, Zhigang; Deng, Wei; Chen, Guangyong; Xu, Rui; Wei, Qi; Liu, Yishan; Han, Jiagang; Li, Ang; et al. (Frontiers in Oncology, 2023)
Background: Neoadjuvant chemoradiotherapy is the standard treatment for locally advanced rectal cancer, with modest benefits on tumor regression and survival. Since chemoradiotherapy combined with immune checkpoint inhibitors has been reported to have synergic effects. This study aims to explore the safety and efficacy of long-course chemoradiotherapy combined with concurrent tislelizumab as a neoadjuvant treatment regimen for patients with locally advanced rectal cancer. Methods: This manuscript reported the interim result of a prospective, multicenter, single-arm, phase II trial. Patients with mid-to-low locally advanced rectal cancer with clinical stages of cT3-4a N0M0 or cT1-4a N1-2M0 were included. The patients received long-course radiotherapy (50 Gy/25 f, 2 Gy/f, 5 days/week) and three 21-day cycles of capecitabine (1000 mg/m2, bid, day1-14) plus concurrent three 21-day cycles of tislelizumab (200 mg, day8), followed by a radical surgery 6-8 weeks after radiotherapy. The primary endpoint was the pathological complete response rate. (Clinical trial number: NCT04911517) Results: A total of 26 patients completed the treatment protocol between April 2021 and June 2022. All patients completed chemoradiotherapy, 24 patients received three cycles of tislelizumab, and 2 patients received two cycles. The pathological complete remission (ypT0N0) was achieved in 50% (13/26) of the patients with all proficient mismatch repair tumors. The immune-related adverse event occurred in 19.2% (5/26) of patients. Patients with no CEA elevation or age less than 50 were more likely to benefit from this treatment regimen. Conclusion: Long-course chemoradiotherapy combined with concurrent tislelizumab in patients with locally advanced low rectal cancer had favorable safety and efficacy, and does not increase the complication rate of surgery. Further study is needed to confirm these results.